Implementasi Media PUZDAYA (Puzzle Budaya) dalam Mengenalkan Literasi Budaya Madura pada Anak Usia Dini - Laili, Faidatul; Musayyadah, Musayyadah; Farida, Siti (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study aims to describe the application of Puzdaya (Cultural Puzzle) media to introduce Madurese cultural literacy to children aged 5-6 years at PGRI II Jrengik Kindergarten. Using a qualitative descriptive approach, data collection was carried out through observation, interviews, and documentation. The results of the study showed that Puzdaya was able to increase children's interest and involvement in learning local culture through interactive activities. The media effectively supports the development of language, motor, social emotional, and cognitive skills. It is concluded that Puzdaya is a meaningful media and in accordance with children's development to strengthen cultural literacy and local identity in early childhood education. as expressed by Ahmad Susanto that the right choice of media in learning is important for the success of a learning process, if teachers are able to do that, students will be motivated and committed to being actively involved in class and therefore puzdaya media (cultural puzzle) is one of the educational media designed to help children recognize elements of local culture through the activity of arranging pictures so that puzdaya not only introduces cultural identity but also strengthens children's attachment to their socio-cultural environment